(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the current state of 4C technology (creativity, critical thinking, communication, and cooperative learning) in the development of spatial visualization skills among primary school students, and explores novel methods to improve this process. Based on Uzbek and international pedagogical experience, the investigation points out the content, didactic potential, and educational effectiveness of visual, interactive, and competency-based approaches in teaching spatial shapes. In addition, a comparison study of conventional instructional techniques and 4C technology-based approaches is conducted, substantiating the significance of creative tasks, problem-based situations, collaborative activities, and visual modeling in the development of spatial visualization skills. The findings identify methodological directions that further improve the process of developing spatial visualization skills in primary education practice. The study proposes practical methodological guidelines for integrating 4C technology into primary mathematics lessons and may be useful for teachers seeking to enhance students’ spatial thinking skills.